Scientific idea and organization of the faculty of clinical psychology and psychotherapy in Siberian State Medical University - N. A. Kornetov (Бюллетень сибирской медицины)
In the paper the starting positions of educational process at the faculty of clinical psychology and psychotherapy in Siberian State Medical University have been stated. The modern ideas of environment factors influence on gene expression are advanced as a natural scientific basis of educational way. And, correspondingly, the ideas of social environment influence on the character of neuromediator impact on an organism. The educational idea has been built on the balanced ratio of the humanities and neuro-sciences. The central place in the first-years education will be taken by academic psychology accented on the experimental methods, and in the senior years education — study of empirical and germenevtic psychology in their interaugmentability and enrichment. The contemporary image of the faculty and its ways of development have been presented.